The Effect of Using Mind Mapping Strategy towards Students’ Learning Activities - Ristiliana Ristiliana; Nurasmawi Nurasmawi; Dicki Hartanto; Akhyar Akhyar; Indri Yuliana (STAI Hubbulwathan Duri, 2022)
This research aimed to investigate the effect of using Mind mapping towards Students’ learning activities on Economic at State Senior High School 1 Kampar. Grade X1, which consisted of 34 students, was selected as sample and was assigned as the experimental group that received treatment while X2, which consisted of 33 students, was assigned as control group. The data of this experimental research were collected through observation and documentation. Further, those data were analysed whit T-test. Based on the results, there was a significant effect of using Mind mapping strategy towards students’ learning activities on economic with higher percentage than control group.